Acute glomerulonephritis, rapidly progressive emphasis on commitment (Colombia Medica, 2024)
Acute glomerulonephritis (GNA) is a wide group of diseases with the common characteristics of abrupt onset and proliferation of endocapillary glomerular cells. Clinically, they usually manifest as acute nephritic syndrome: hematuria, acute renal failure, hypertension and mild proteinuria, although they can appear as recurrent hematuria. GNA can be present in association with a variety of bacterial and viral infections, but in most cases the initial antigenic initiating stimulus is unknown. Patients with rapidly progressive glomerulonephritis often present acute onset of manifestations of nephritis, such as azotemia, oliguria, edema, hypertension, proteinuria, and hematuria with «active» urine sediment that often contains red blood cell casts, pigmented casts, and cellular debris. This article, aimed at all primary care staff and seeking to increase their awareness of this disease, discusses in more detail the clinical, pathogenesis, pathology, and treatments available from one of the glomerulonephritis with greater impact on survival patient.